Human Resource Management Strategy for Optimizing Elementary School Teacher Professionalism - Darmawan, Andi; Hasanah, Enung; Zuhaery, Muhammad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the Human Resources (HR) management strategy in optimizing teacher professionalism at Muhammadiyah Condongcatur Elementary School. Teacher professionalism is a key pillar in ensuring the quality of education at the elementary school level, but the challenges of curriculum dynamics and workload require a comprehensive managerial strategy. This study uses a qualitative approach with a case study. Data were collected through in-depth interviews with the Principal, Vice Principal, and Teachers, as well as observations, and supported by documentation studies. Data analysis was conducted with the help of the Atlas.ti 9 software to map the relationships between managerial variables. The results show that the HR management strategy is carried out through an integrated cycle, including: 1) Linearity-based planning and real needs analysis; 2) Competency development through applied training and inter-disciplinary collaboration; 3) Reflection-based performance evaluation for policy making; and 4) Internalization of Islamic organizational culture as a reinforcement of moral integrity. Although the reward system has been implemented, the aspect of transparency remains a note for future development. In conclusion, the synergy between administrative support, sustainable capacity development, and spiritual values is key to creating a solid ecosystem of teacher professionalism in elementary schools.